A twist on an old problem

Calculus Level 5

0 π e x x 3 cos 2 x d x \large \displaystyle \int \limits_{0}^{\pi} e^x x^3 \cos^2 x \, dx

The above integral can be expressed in the form 3 625 [ a + e π ( b π 3 + c π 2 + d π a ) ] \dfrac{3}{625} [ a + e^\pi (b \pi^3 + c\pi^2 + d \pi - a)] , where e = lim n ( 1 + 1 n ) n e = \displaystyle \lim_{n \to \infty} \left( 1+ \dfrac{1}{n} \right)^n . Find the value of a + b + c + d a + b + c + d .


The answer is 1038.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We will need the following result: x 3 e a x d x = ( 1 a x 3 3 a 2 x 2 + 6 a 3 x 6 a 4 ) e a x + C \displaystyle \int x^3 e^{ax} dx = \left(\dfrac{1}{a}x^3-\dfrac{3}{a^2}x^2+\dfrac{6}{a^3}x-\dfrac{6}{a^4}\right)e^{ax}+C , and the identity cos 2 x = 1 2 + 1 2 cos ( 2 x ) \cos^2 x = \dfrac{1}{2}+\dfrac{1}{2}\cos(2x) .

Let I = 1 2 0 π e x x 3 d x \displaystyle I = \dfrac{1}{2} \int_0^\pi e^x x^3 dx and J = 1 2 0 π e x x 3 cos ( 2 x ) d x \displaystyle J=\dfrac{1}{2} \int_0^\pi e^x x^3 \cos(2x) dx , so the answer will be I + J I+J .

We have:

I = 1 2 [ ( x 3 3 x 2 + 6 x 6 ) e x ] 0 π = 1 2 [ e π ( π 3 3 π 2 + 6 π 6 ) + 6 ] \displaystyle I = \dfrac{1}{2}\left[(x^3-3x^2+6x-6)e^x \right] \Big|_0^\pi = \dfrac{1}{2}\left[e^\pi(\pi^3-3\pi^2+6\pi-6)+6\right]

J = 1 2 Re [ 0 π e x x 3 e 2 x i d x ] = 1 2 Re [ 0 π x 3 e ( 1 + 2 i ) x d x ] \displaystyle J = \dfrac{1}{2} \text{Re} \left[ \int_0^\pi e^x x^3 e^{2xi} dx \right] = \dfrac{1}{2} \text{Re} \left[ \int_0^\pi x^3 e^{(1+2i)x} dx \right]

Let a = 1 + 2 i a=1+2i , then, in polar form, a = a e θ i a=\lvert a \rvert e^{\theta i} . Then: J = 1 2 Re [ ( x 3 a 3 x 2 a 2 + 6 x a 3 6 a 4 ) e ( 1 + 2 i ) x ] 0 π = 1 2 a 8 Re [ ( a 7 e θ i x 3 3 a 6 e 2 θ i x 2 + 6 a 5 e 3 θ i x 6 a 4 e 4 θ i ) e ( 1 + 2 i ) x ] 0 π = 1 2 a 8 Re [ ( a 7 e ( 2 x θ ) i x 3 3 a 6 e ( 2 x 2 θ ) i x 2 + 6 a 5 e ( 2 x 3 θ ) i x 6 a 4 e ( 2 x 4 θ ) i ) e x ] 0 π = 1 2 a 8 [ ( a 7 cos ( 2 x θ ) x 3 3 a 6 cos ( 2 x 2 θ ) x 2 + 6 a 5 cos ( 2 x 3 θ ) x 6 a 4 cos ( 2 x 4 θ ) ) e x ] 0 π = 1 2 a 8 [ ( a 7 cos ( θ ) π 3 3 a 6 cos ( 2 θ ) π 2 + 6 a 5 cos ( 3 θ ) π 6 a 4 cos ( 4 θ ) ) e π + 6 a 4 cos ( 4 θ ) ] \begin{aligned} J &= \dfrac{1}{2} \text{Re} \left[ \left( \dfrac{x^3}{a}-\dfrac{3x^2}{a^2}+\dfrac{6x}{a^3}-\dfrac{6}{a^4} \right) e^{(1+2i)x} \right] \Big|_0^\pi\\ &= \dfrac{1}{2|a|^8} \text{Re} \left[ \left( |a|^7 e^{-\theta i} x^3-3|a|^6 e^{-2\theta i} x^2+6|a|^5 e^{-3\theta i} x-6|a|^4 e^{-4\theta i} \right) e^{(1+2i)x} \right] \Big|_0^\pi\\ &= \dfrac{1}{2|a|^8} \text{Re} \left[ \left( |a|^7 e^{(2x-\theta) i} x^3-3|a|^6 e^{(2x-2\theta) i} x^2+6|a|^5 e^{(2x-3\theta) i} x-6|a|^4 e^{(2x-4\theta) i} \right) e^x \right] \Big|_0^\pi\\ &= \dfrac{1}{2|a|^8} \left[ \left( |a|^7 \cos(2x-\theta) x^3-3|a|^6 \cos(2x-2\theta) x^2+6|a|^5 \cos(2x-3\theta) x-6|a|^4 \cos(2x-4\theta) \right) e^x \right] \Big|_0^\pi\\ &= \dfrac{1}{2|a|^8} \left[ \left( |a|^7 \cos(\theta) \pi^3-3|a|^6 \cos(2\theta) \pi^2+6|a|^5 \cos(3\theta) \pi-6|a|^4 \cos(4\theta) \right) e^\pi + 6|a|^4 \cos(4\theta) \right] \end{aligned} But a 2 = 3 + 4 i a^2=-3+4i , a 3 = 11 2 i a^3=-11-2i and a 4 = 7 24 i a^4=-7-24i , so cos ( θ ) = 1 a \cos(\theta)=\dfrac{1}{|a|} , cos ( 2 θ ) = 3 a 2 \cos(2\theta)=-\dfrac{3}{|a|^2} , cos ( 3 θ ) = 11 a 3 \cos(3\theta)=-\dfrac{11}{|a|^3} and cos ( 4 θ ) = 7 a 4 \cos(4\theta)=-\dfrac{7}{|a|^4} . Then: J = 1 2 a 8 [ ( a 6 π 3 3 a 4 ( 3 ) π 2 + 6 a 2 ( 11 ) π 6 ( 7 ) ) e π + 6 ( 7 ) ] = 1 1250 [ ( 125 π 3 + 225 π 2 330 π + 42 ) e π 42 ] \begin{aligned} J &= \dfrac{1}{2|a|^8} \left[ \left( |a|^6 \pi^3-3|a|^4 (-3) \pi^2+6|a|^2 (-11) \pi-6(-7) \right) e^\pi + 6(-7) \right]\\ &= \dfrac{1}{1250} \left[ \left(125\pi^3+225\pi^2-330\pi+42 \right) e^\pi - 42 \right] \end{aligned} Finally: I + J = 3 625 [ 618 + e π ( 125 π 3 275 π 2 + 570 π 618 ) ] I+J = \dfrac{3}{625}\left[ 618+e^\pi(125\pi^3-275\pi^2+570\pi-618) \right] . Then, a = 618 a=618 , b = 125 b=125 , c = 275 c=-275 , d = 570 d=570 and a + b + c + d = 1038 a+b+c+d=\boxed{1038} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...